2017
DOI: 10.1007/s40195-017-0598-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of the Nickel-Based Superalloy DZ125 at 980 °C

Abstract: The isothermal oxidation behavior of the nickel-based superalloy DZ125 was investigated at 980°C through SEM/EDX and XRD. The weight loss process exhibited three periods-initial, transient and steady stages, which correspond to the formation of three layers on the surface. The outer layer was composed of NiO, whereas the intermediate layer mainly consisted of spinels and was accompanied with Ta-rich oxide. Alumina was evident as the inner continuous layer close to the substrate. The first formation of alumina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…2) suggesting the cracking followed a start-stop-start process, but no evidence of fatigue striations could be found during the SEM examination. EDX mapping, on the unetched longitudinal sections, of the hot corrosion products within the CMSX-4 and CM247LC DS cracks that were remote from the final fracture, revealed an O [21] and S [20] embrittled phase (Fig. 3 shows an example from CMSX-4).…”
Section: Resultsmentioning
confidence: 99%
“…2) suggesting the cracking followed a start-stop-start process, but no evidence of fatigue striations could be found during the SEM examination. EDX mapping, on the unetched longitudinal sections, of the hot corrosion products within the CMSX-4 and CM247LC DS cracks that were remote from the final fracture, revealed an O [21] and S [20] embrittled phase (Fig. 3 shows an example from CMSX-4).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a large number of secondary cracks in alloy 4 indicate that the binding force of grain boundaries has been weakened seriously. In crack initiation stage, it is believed that oxide cracking can result in crack initiation, which shortens the stress rupture life [25,26]. Therefore, oxygen atoms may diffuse along grain boundaries and bring in the grain boundary oxidation because the stress rupture samples are exposed to high-temperature field and stress field for a long time.…”
Section: Mechanical Role Of Fe and Pmentioning
confidence: 99%
“…Therefore, one of the methodologies to improve the stress and creep properties of Ni-based alloys is to add phosphorus into superalloys. Sun et al found that the addition of phosphorus promoted the precipitation of M 23 C 6 and M 3 B 2 and thus enhanced the stress-rupture life of GH761 [4][5][6]. It was also reported that phosphorus was dissolved in the c matrix of IN706 alloy and accelerated the precipitation of c 0 phase [7], which indicated that the effect of phosphorus on intragranular precipitates was of great importance.…”
Section: Introductionmentioning
confidence: 98%